Evangelisasi dan Pendidikan Agama Kristen: Pendidikan Minat dan Pemahaman Injil Generasi Milenial Pantekosta - Hesra Oktavianus Sembiring; Elia Tambunan; Andreas Sudjono (Jurnal Shanan, 2022)
The current trend of the world church is in the crisis of the millennial generation who are running away from the church, this paper actually displays the education of interest and understanding of the gospel for the Pentecostal millennial generation to be involved in evangelization by imitating Jesus. The research was conducted with a quantitative approach. Data were collected through a questionnaire with a Likert scale, analyzed by Pearson Product Moment correlation using the statistical formula for Confidence Interval Lower and Upper Bound values. The research locus of the Salatiga College of Theology, Central Java, and the respondents are students in 2018-2020 as many as 65 people in semesters 4 and 6 who have taken the Bible Tafsir John 4:1-42 and Evangelical Practice courses. The findings show that doctrinal learning efforts by lecturers, both academic and non-academic as well as institutional culture, support the formation of Christian religious higher education praxis. This paper proposes a new conceptual framework, namely interest and understanding education, for mission pedagogy in Christian Religious Education and mission theology in the Theology study program.